Safety Design using ATS by Identifying Voltage Interference based on Fuzzy Logic - RAKHMAWATI, RENNY; RAHARJA, LUCKY PRADIGTA SETIYA; HUSNAH, MANICHA MIFTACHUL (Institut Teknologi Nasional, Bandung, 2023)
ABSTRAKSumber energi listrik PLN merupakan sumber utama bagi masyarakat. Namun kenyataan saat ini PLN masih belum maksimal dalam menyalurkan energi seperti dapat terjadi pemadaman, dan fluktuasi tegangan yang merupakan gangguan tegangan AC. Gangguan tegangan sendiri dapat menyebabkan kerusakan pada beban rumah tangga. Oleh karena itu, dalam jurnal ini membuat suatu inovasi dengan memanfaatkan sumber dari Baterai yang berfungsi untuk membackup ketika sumber PLN mengalami pemadaman dan gangguan. Dengan mengembangkan sistem yaitu automatic transfer switch (ATS) yang dapat membuat beban dalam kondisi aman dan mendapatkan aliran energi dari sumberÂ cadangan. Sistem ini bekerja dengan mendeteksi 6 gangguan tegangan AC dengan metode fuzzy logic. Gangguan tersebut antara lain Interruption, Sag, Swell, Sustained Interruption, Undervoltage, dan Overvoltage. Dan sistem ATS bekerja saat jenis gangguan Durasi Panjang yaitu Sustained Interruption, Undervoltage, dan Overvoltage. Sistem automatic transfer switch ini mampu melakukan perpindahan sumber dalam waktu 5ms.Kata kunci: Automatic Transfer switch, Fuzzy Logic, Gangguan AC, PLNÂ ABSTRACTThe primary source of electricity is PLN. However, the current situation shows that PLN is still not doing its best to distribute energy, as seen by blackouts and voltage fluctuations, which are disturbances of the AC voltage. Household loads can damaged by voltage disruptions. As a result, an innovation is made in this journal by utilizing the battery source, which serves as a backup when the PLN source encounters a blackout and other disruption. By developing a system, namely an automated transfer switch (ATS), that can maintain loads in a safe condition and allow energy to flow from backup sources The fuzzy logic method is used to identify six AC voltage disturbances in this system. There are six of AC voltage disturbances: interruption, sag, swell, sustained interruption, undervoltage, and overvoltage. The ATS system functions when there is a long duration disturbance,Â such as a sustained interruption, undervoltage, or overvoltage. This automatic transfer switch system has a switching time of 5 milliseconds.Keywords: Automatic Transfer switch, Fuzzy Logic, Voltage Disruption, PLN